An Excel Tool to Assess Acquisition Program Risk - Mayer, Lauren A. (RAND Corporation, 2013)
Implementing risk management principles for large defense acquisition programs is a priority for the U.S. defense acquisition community. To assist decisionmakers responsible for identifying major weapons programs' risks, RAND developed a methodology, an Excel risk tool (the "Assessor Tool"), and this users' manual. The tool offers an approach to the evaluation of system integration risk for defense staff assessors.